2010
DOI: 10.1002/ejic.201000815
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular and Intramolecular Energy Transfer with Ruthenium–Anthracene Donor–Acceptor Couples: Salt Bridge versus Covalent Bond

Abstract: The formation of hydrogen‐bonded cation–anion adducts between the complex [Ru(bpy)2(biimH2)]2+ (bpy = 2,2′‐bipyridine; biimH2 = 2,2′‐biimidazole) and anthracene‐9‐carboxylate in dichloromethane solution was investigated by 1H NMR, optical absorption, and luminescence spectroscopy. The experimental data indicates that more than one anthracene‐9‐carboxylate anion can interact closely with the dicationic ruthenium complex. Energy transfer from the photoexcited ruthenium complex to anthracene‐9‐carboxylate in 1:1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…Earlier Beauchamp and co‐workers had shown that rhenium(III) complexes with biimidazole ligands not only bind halide anions via hydrogen bonds but also form hydrogen bond networks with benzoate anions . Energy transfer processes between metal complexes as well as organic triplet emitters and metal complexes have also been observed for hydrogen bonded systems which consisted of the biimidazole‐carboxylate motive . We were able to show that DNB quenches the phosphorescence of 12 by about 50 % in a 1:1 mixture in chloroform, and further addition of up to 8 equivalents leads to a residual luminescence of only about 8 % with respect to the pristine complex.…”
Section: Sensors For Small Anionssupporting
confidence: 52%
“…Earlier Beauchamp and co‐workers had shown that rhenium(III) complexes with biimidazole ligands not only bind halide anions via hydrogen bonds but also form hydrogen bond networks with benzoate anions . Energy transfer processes between metal complexes as well as organic triplet emitters and metal complexes have also been observed for hydrogen bonded systems which consisted of the biimidazole‐carboxylate motive . We were able to show that DNB quenches the phosphorescence of 12 by about 50 % in a 1:1 mixture in chloroform, and further addition of up to 8 equivalents leads to a residual luminescence of only about 8 % with respect to the pristine complex.…”
Section: Sensors For Small Anionssupporting
confidence: 52%
“…Inspired by Fe(II) biimidazoline complexes which had been used successfully for investigations of ground-state PCET, 4,29,30 photoactive d 6 metal complexes of 2,2'-biimidazole were therefore investigated in the context of excited-state PCET. [31][32][33] From early studies by Haga it was known that biimidazole complexes of Ru(II) and Os(II) exhibit long-lived 3 MLCT states from which electron and proton donation occurs more readily than from the ground state. 34 Given the proximity of the N-H functions to the metal center it was hoped that deprotonation could be monitored by optical spectroscopy, and this was in fact one of the key motivations for this work.…”
Section: Photoexcited Complexes As Comined Electron/proton Donorsmentioning
confidence: 99%
“…9,[26][27][28][29][30] (3) Hydrogen bonds, where the sensitizer and PCET reactant are brought together through a hydrogen bond. 3,[31][32][33][34] The use of covalent and hydrogen bonds in ES-PCET has facilitated large gains in the fundamental understanding of ES-PCET. One large convenience afforded through the latter two methods is that the removal of reactant diffusion allows direct measurement of the ES-PCET reaction rate constants.…”
Section: Introductionmentioning
confidence: 99%